Frequency of Hepatitis-D in HbsAg Positive Cases at Peoples University of Medical & Health Sciences for Women Hospital Nawabshah (Medical Forum Monthly, 2024)
Objective: To find out the frequency of delta virus (HDV) in HBV positive patientsStudy Design: Observational StudyPlace and Duration of study: This study was conducted at the Department of Medicine PUMHS Nawabshah form 01-01-2011 to 31-12-2011.Materials and Methods: 200 adult patents of conformed Hepatitis B were included in the study blood samples of all the patients were screened for HDV by Elisa method / PCR during period of one yare.Clinical status of positive and negative patients was also compared.Results: Anti HDV was found in 32 patients (15%1) among them 20 (62%) were male and 12 (38%) were female.Conclusion: The prevalence of HDV infection in HBV +ve patients is significant our area.Primary eradication of Hepatitis B virus is required